(untitled) (Research, Society and Development, 2022)
The agro-industrial systems comprise activities which transform raw materials of agricultural, aquacultural, livestock and forestry industries from primary production stages to consumption. Pig farming stands out in national and international markets for agro-industrial processes such as slaughtering and meat processing. Although this sector positively contributes to the economies of several countries, the high flow of waste resulting from implementing integrated production systems has led to serious environmental consequences (e.g., polluted water bodies and Greenhouse Gases - GHGs emissions). Among the treatment methods, anaerobic digestion reduces the organic load of biomass in the absence of oxygen, generating biogas and organic fertilizer. However, there are limitations associated with high CH4 variability and low yield, resulting a minimal and slow implementation in Brazil. Some research has reported the use of mineral additives to optimize the digestion process. This study comprises a bibliographic review of pig farming systems and production models, followed by an analysis on a global scale and environmental consequences. It is also discussed the use of additive minerals which have been applied in anaerobic digestion of swine manure as well as some prospects for global advances with opportunities to mitigate GHGs and bottlenecks. Despite being a promising technology, detailed evaluations of the use of these additives and their implementation in treatment plants must still be carried out in such a way to understand the optimization of such process.